A polyurethane potting adhesive with high thermal conductivity and low expansion coefficient and preparation method thereof

By developing a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, the heat accumulation and expansion problems caused by poor thermal conductivity in high-voltage DC transmission systems are solved, and a longer equipment service life and more stable system operation are achieved.

CN119286463BActive Publication Date: 2025-04-04JINAN XIDIAN SPECIAL TRANSFORMER CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411838386.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-04
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

In high-voltage DC transmission systems, the silicon steel sheets in the saturated reactor generate a large amount of heat during high load or overload. If the thermal conductivity of the potting material is poor, it cannot export heat in time, resulting in a shortening of the service life of the equipment and may cause cracks and charge accumulation in the insulating shell, affecting the stable operation of the system.

Method used

A polyurethane potting glue with high thermal conductivity and low expansion coefficient was developed. Polyurethane potting glue with high thermal conductivity and low expansion properties were prepared by using components such as epoxy soybean oil modified polyether polyol, modified castor oil, inorganic filler and polymerized MDI, combined with specific process steps such as heating and stirring, water removal and vacuum defoaming.

Benefits of technology

This polyurethane potting adhesive can effectively conduct heat, reduce heat accumulation, reduce expansion risks, extend equipment service life, and improve system stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention provides a polyurethane potting compound with high thermal conductivity and low coefficient of thermal expansion and its preparation method, comprising components A and B. Component A includes 60-90 parts of epoxidized soybean oil modified polyether polyol with a molecular weight of 4000-6000 and a functionality of 2.5-4.5, 20-50 parts of modified castor oil, 20-50 parts of inorganic filler, and 1-3 parts of pigment. The modified castor oil is at least one of succinic acid modified castor oil, hydrogenated castor oil, and epoxidized castor oil. The modified castor oil has a molecular weight of 900-1800 and a hydroxyl value of 160-200 mgKOH / g. The inorganic filler includes calcium carbonate and nano-inorganic materials. Component B is polymeric MDI. The above-mentioned modified castor oil and epoxidized soybean oil modified polyether polyol have fewer effective functional groups in their molecular structure, and the molecules undergo little unentanglement after heating, resulting in low shrinkage or expansion due to gradual polymerization. Combined with inorganic filler, the potting compound exhibits high thermal conductivity and a low coefficient of thermal expansion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane potting adhesives, and in particular relates to a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient and a preparation method thereof. Background Art

[0002] With the development and application of high-voltage direct current transmission technology, converter valves as core equipment have received more and more attention. Among them, saturated reactors are key components to ensure the normal conduction and shutdown of the thyristors inside them. When the converter valve is under high load or overload, the silicon steel sheets in the saturated reactor will generate a lot of heat in a short time. The heat will accumulate in the equipment in a short time. If the thermal conductivity of the potting material in the saturated reactor is poor, the heat cannot be discharged in time, which seriously affects the service life of the electrical equipment. The accumulation of heat will also cause thermal expansion of the potting material. If the expansion coefficient is too large, cracks will appear in the insulating shell. Charge accumulation will occur at the cracks. The accumulated charge is not easy to dissipate under ultra-high / ultra-high DC voltage, resulting in serious distortion of the electric field on the surface of the solid insulation, which manifests as local insulation failure and threatens the smooth operation of the entire DC transmission system. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient and a preparation method thereof. The polyurethane potting adhesive has high thermal conductivity, low expansion coefficient, good insulation, low viscosity, strong damping performance, etc., and is suitable for saturated reactors.

[0004] The present invention provides a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising component A and component B;

[0005] In parts by weight, the component A comprises 60-90 parts of epoxy soybean oil-modified polyether polyol, 20-50 parts of modified castor oil, 20-50 parts of inorganic filler and 1-3 parts of pigment;

[0006] The molecular weight of the epoxy soybean oil-modified polyether polyol is 4000-6000, and the functionality is 2.5-4.5;

[0007] The modified castor oil is succinic acid-modified castor oil, hydrogenated castor oil or epoxidized castor oil; the molecular weight of the modified castor oil is 900-1800, and the hydroxyl value is 160-200 mgKOH / g;

[0008] The B component is polymeric MDI.

[0009] Preferably, the particle size of the nano inorganic substance is 100-500 nm;

[0010] The mass ratio of the calcium carbonate to the nano-inorganic matter is 1-3:1.

[0011] Preferably, the nano-inorganic substance is selected from one or more of nano-aluminum oxide, nano-silicon carbide and nano-aluminum nitride.

[0012] Preferably, the mass content of isocyanate in polymeric MDI is 20-35%.

[0013] Preferably, the mass ratio of component A to component B is 7.8-8.2:1.

[0014] The present invention provides a method for preparing the polyurethane potting adhesive with high thermal conductivity and low expansion coefficient described in the above technical solution, comprising the following steps:

[0015] The epoxy soybean oil-modified polyether polyol, modified castor oil, inorganic filler and pigment are mixed, heated to 80-120° C., stirred for 0.5-1.5 h, and then water is removed to obtain component A;

[0016] After the component A and the component B are mixed, the mixture is evacuated to -0.095-0.1 Mpa, stirred evenly at 600-1200 rpm, degassed, and cured to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0017] The invention provides a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising a component A and a component B; in parts by weight, the component A comprises 60-90 parts of epoxy soybean oil-modified polyether polyol, 20-50 parts of modified castor oil, 20-50 parts of inorganic filler and 1-3 parts of pigment; the epoxy soybean oil-modified polyether polyol has a molecular weight of 4000-6000 and a functionality of 2.5-4.5; the modified castor oil is succinic acid-modified castor oil, hydrogenated castor oil or epoxidized castor oil; the modified castor oil has a molecular weight of 900-1800 and a hydroxyl value of 160-200 mgKOH / g; the inorganic filler comprises calcium carbonate and nano inorganic matter; and the component B is polymerized MDI. The polyether polyol modified by the modified castor oil and epoxidized soybean oil of the above types adopted in the present invention has few effective functional groups in the molecular structure, and the molecules undergo little disentanglement after being heated, and the shrinkage or expansion caused by gradual polymerization is low; combined with the use of the above-mentioned inorganic filler, the polyurethane potting adhesive has the performance of high thermal conductivity and low expansion coefficient. DETAILED DESCRIPTION

[0018] The present invention provides a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising component A and component B;

[0019] In parts by weight, the component A comprises 60-90 parts of epoxy soybean oil-modified polyether polyol, 20-50 parts of modified castor oil, 20-50 parts of inorganic filler and 1-3 parts of pigment;

[0020] The molecular weight of the epoxy soybean oil-modified polyether polyol is 4000-6000, and the functionality is 2.5-4.5;

[0021] The modified castor oil is one or more of succinic acid-modified castor oil, hydrogenated castor oil and epoxidized castor oil; the molecular weight of the modified castor oil is 900-1800, and the hydroxyl value is 160-200 mgKOH / g;

[0022] The inorganic filler includes calcium carbonate and nano inorganic matter;

[0023] The B component is polymeric MDI.

[0024] The present invention selects epoxy soybean oil-modified polyether polyols with specific functionality and molecular weight, specific types of modified castor oil and polymerized MDI for reaction, does not use a catalyst, does not add solvents and plasticizers, has low viscosity, long operability time, moderate hardness and softness after curing, good thermal conductivity, and low expansion coefficient, and is suitable for high thermal conductivity and low expansion potting of saturated reactors; it also ensures the cross-linking density of the sample after curing, so that it has a certain hardness and can ensure toughness.

[0025] The polyurethane potting adhesive with high thermal conductivity and low expansion coefficient provided by the present invention comprises component A. The raw materials for preparing component A comprise 60 to 90 parts of polyether polyol modified with epoxy soybean oil in parts by weight; the specific amount can be 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts or 90 parts. The molecular weight of the epoxy soybean oil-modified polyether polyol is 4000-6000, the functionality is 2.5-4.5, and the hydroxyl value is 30-50 mgKOH / g. The present invention adopts the epoxy soybean oil-modified polyether polyol with the above functionality and molecular weight, which has moderate viscosity and is conducive to practical operation. The specific functionality ensures the cross-linking density of the sample after curing, so that it has a certain hardness while ensuring its toughness.

[0026] In a specific embodiment, the molecular weight of the epoxy soybean oil-modified polyether polyol is 4800, 5500, 6000 or 4000; and the functionality is 3.

[0027] The A component includes 20 to 50 parts of modified castor oil, and the specific amount is 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts; the modified castor oil is one or more of succinic acid modified castor oil, hydrogenated castor oil and epoxidized castor oil. The molecular weight of the modified castor oil is 900 to 1800, and the hydroxyl value is 160 to 200 mgKOH / g. The present invention adopts the above-mentioned modified castor oil to further improve the hardness of the polyurethane potting glue. Castor oil belongs to natural plant oleic acid, has good biodegradability, and is a green and environmentally friendly raw material.

[0028] In a specific embodiment, the modified castor oil is selected from one or more of succinic acid modified castor oil with a molecular weight of 1500 and a hydroxyl value of 165 mgKOH / g; hydrogenated castor oil with a molecular weight of 1800 and a hydroxyl value of 167 mgKOH / g; epoxidized castor oil with a molecular weight of 1000 and a hydroxyl value of 175 mgKOH / g; epoxidized castor oil with a molecular weight of 1000 and a hydroxyl value of 192 mgKOH / g; hydrogenated castor oil with a molecular weight of 1500 and a hydroxyl value of 200 mgKOH / g and succinic acid modified castor oil with a molecular weight of 1800 and a hydroxyl value of 160 mgKOH / g.

[0029] The A component includes 20 to 50 parts of inorganic filler; the specific amount can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts. The inorganic filler includes calcium carbonate and nano inorganic material; the particle size of the nano inorganic material is 100 to 500nm; the mass ratio of the calcium carbonate to the nano inorganic material is 1 to 3:1. The nano inorganic material is selected from one or more of nano alumina, nano silicon carbide and nano aluminum nitride. In a specific embodiment, the particle size of nano aluminum nitride is 120-150 nm, the particle size of nano silicon carbide is 450-500 nm, and the particle size of nano aluminum oxide is 200-300 nm or 100-120 nm. In a specific embodiment, the inorganic filler is a mixture of calcium carbonate, aluminum nitride, silicon carbide and aluminum oxide in a mass ratio of 10:15:10:5; or a mixture of calcium carbonate, aluminum nitride and silicon carbide in a mass ratio of 10:15:10; or a mixture of calcium carbonate and silicon carbide in a mass ratio of 10:40; or a mixture of calcium carbonate and aluminum oxide in a mass ratio of 10:10. The compound use of calcium carbonate and the above-mentioned types of nano inorganic substances in the present invention can form more heat conduction channels and heat conduction interfaces, thereby improving the thermal conductivity of the polyurethane potting glue. Nano inorganic substances of different particle sizes are mixed with calcium carbonate, and the mixture is more uniform, thereby ensuring the uniformity of the performance of the polyurethane potting glue.

[0030] The polyether polyol modified by the modified castor oil and epoxidized soybean oil of the above types adopted in the present invention has few effective functional groups in the molecular structure, and the molecules undergo little disentanglement after being heated, and the shrinkage or expansion caused by gradual polymerization is low; combined with the use of the above-mentioned inorganic filler, the polyurethane potting adhesive has the performance of high thermal conductivity and low expansion coefficient.

[0031] The A component includes 1 to 3 parts of pigment, and the amount can be specifically 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts; the pigment is selected from one or more of iron red, iron blue and iron yellow.

[0032] In a specific embodiment, the component A includes 20 parts of succinic acid-modified castor oil, 60 parts of epoxy soybean oil-modified polyether polyol, 20 parts of inorganic filler, 1 part of iron blue, and 1 part of iron yellow;

[0033] Or comprising 50 parts of hydrogenated castor oil, 90 parts of polyether polyol modified by epoxy soybean oil, 50 parts of inorganic filler, and 3 parts of iron red;

[0034] Or comprising 20 parts of epoxidized castor oil, 75 parts of polyether polyol modified by epoxidized soybean oil, 35 parts of inorganic filler, and 1 part of iron red;

[0035] Or including 10 parts of epoxidized castor oil, 15 parts of hydrogenated castor oil, 10 parts of succinic acid-modified castor oil, 80 parts of polyether polyol modified by epoxidized soybean oil, 40 parts of inorganic filler, 1 part of iron blue, 1 part of iron yellow and 1 part of iron red.

[0036] The polyurethane potting adhesive with high thermal conductivity and low expansion coefficient provided by the present invention comprises a B component, wherein the B component is polymerized MDI. The mass content of isocyanate in the polymerized MDI is 20-35%; the content can be specifically 20%, 21%, 22%, 23%, 24%, 25%, 26%, 7%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%.

[0037] The mass ratio of component A to component B in the present invention is 7.8-8.2:1, preferably 8:1.

[0038] The present invention provides a method for preparing the polyurethane potting adhesive with high thermal conductivity and low expansion coefficient described in the above technical solution, comprising the following steps:

[0039] The epoxy soybean oil-modified polyether polyol, modified castor oil, inorganic filler and pigment are mixed, heated to 80-120° C., stirred for 0.5-1.5 h, and then water is removed to obtain component A;

[0040] After the A component and the B component are mixed, the mixture is evacuated to -0.095-0.1 MPa, stirred evenly at 600-1200 rpm, degassed, and cured to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0041] The present invention preferably uses a dispersing mixer to evacuate and remove water, and the dewatering time is 1 to 2 hours. The present invention preferably uses a vacuum degassing method, and the degassing process is repeated 2 to 5 times. The present invention is cured at 65 to 75° C. for 3 to 6 hours or at room temperature for 24 to 48 hours.

[0042] The present invention focuses on the technology and quality upgrade of key core components in the current power industry, develops a special high-thermal conductivity potting glue for the packaging of high-performance converter valve saturated reactors, improves the situation of difficult heat dissipation and easy failure due to vibration during the operation of saturated reactors, increases the service life of converter valves, and ensures stable and efficient operation of power equipment.

[0043] In order to further illustrate the present invention, a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0044] Example 1

[0045] A polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising component A and component B;

[0046] Component A comprises the following raw materials in parts by weight: 20 parts of succinic acid-modified castor oil, 60 parts of epoxy soybean oil-modified polyether polyol, 20 parts of inorganic filler, 1 part of iron blue, and 1 part of iron yellow.

[0047] Component B comprises the following preparation raw materials in parts by weight: polymeric MDI.

[0048] The mass ratio of component A to component B is 8:1.

[0049] The castor oil used is succinic acid-modified castor oil with a molecular weight of 1500 and a hydroxyl value of 165 mgKOH / g; the polyether polyol used is polyether polyol modified with epoxy soybean oil with a molecular weight of 4800 and a functionality of 3; and the isocyanate content of the polymerized MDI is 35%.

[0050] The inorganic filler comprises the following raw materials in parts by weight: 10 parts of calcium carbonate and 10 parts of aluminum oxide. The particle size of the aluminum oxide filler is distributed in the range of 100-120 nm.

[0051] The preparation method of the above-mentioned polyurethane potting adhesive with high thermal conductivity and low expansion coefficient comprises the following steps:

[0052] (1) Preparation of component A:

[0053] According to the formula, the modified castor oil, the polyether polyol modified by epoxy soybean oil, the inorganic filler and the pigment in component A are weighed respectively; the weighed components are put into a disperser, the temperature is raised to 90° C., and the disperser is stirred for 1 hour. Then, the disperser is evacuated and stirred to remove water for 1 hour to obtain component A.

[0054] According to the mass ratio of component A to component B of 8:1, weigh component B.

[0055] (2) Preparation of polyurethane potting compound with high thermal conductivity and low expansion coefficient

[0056] After mixing and stirring component A and component B, put them into a vacuum degassing machine, evacuate to -0.1Mpa, and perform vacuum mixing, stirring and degassing at a speed of 600-1000rpm. After the vacuum stirring and degassing process is repeated 3 times, pour them into a mold and cure them at 70°C for 4h to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0057] Example 2

[0058] A polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising component A and component B;

[0059] Component A comprises the following raw materials in parts by weight: 50 parts of hydrogenated castor oil, 90 parts of polyether polyol modified by epoxy soybean oil, 50 parts of inorganic filler, and 3 parts of iron red.

[0060] Component B comprises the following preparation raw materials in parts by weight: polymeric MDI.

[0061] The mass ratio of component A to component B is 8:1.

[0062] The castor oil selected is hydrogenated castor oil with a molecular weight of 1800 and a hydroxyl value of 167 mgKOH / g; the epoxidized soybean oil-modified polyether polyol selected is epoxidized soybean oil-modified polyether polyol with a molecular weight of 5500 and a functionality of 3; and the isocyanate mass content of the polymerized MDI is 20%.

[0063] The inorganic filler comprises the following raw materials in parts by weight: 35 parts of calcium carbonate and 15 parts of silicon carbide. The particle size distribution of the silicon carbide filler is 150-200 nm.

[0064] The preparation method of the above-mentioned polyurethane potting adhesive with high thermal conductivity and low expansion coefficient comprises the following steps:

[0065] (1) Preparation of component A:

[0066] According to the formula, castor oil, epoxy soybean oil-modified polyether polyol, inorganic filler and pigment in component A are weighed respectively; the weighed components are put into a disperser, heated to 100° C., dispersed and stirred for 1 hour, and then the disperser is evacuated and stirred to remove water for 1.5 hours to obtain component A.

[0067] According to the mass ratio of component A to component B of 8:1, weigh component B.

[0068] (2) Preparation of polyurethane potting compound with high thermal conductivity and low expansion coefficient

[0069] After mixing and stirring component A and component B, put them into a vacuum degassing machine, evacuate to -0.1Mpa, and perform vacuum mixing, stirring and degassing at a speed of 600~1000rpm. After the vacuum stirring and degassing process is repeated 4 times, pour them into a mold and cure them at 70℃ for 4h to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0070] Example 3

[0071] A polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising component A and component B;

[0072] Component A comprises the following raw materials in parts by weight: 20 parts of epoxidized castor oil, 75 parts of polyether polyol modified by epoxidized soybean oil, 35 parts of inorganic filler, and 1 part of iron red.

[0073] Component B comprises the following preparation raw materials in parts by weight: polymeric MDI.

[0074] The mass ratio of component A to component B is 8:1;

[0075] The castor oil selected is epoxidized castor oil with a molecular weight of 1000 and a hydroxyl value of 175 mgKOH / g; the epoxidized soybean oil-modified polyether polyol selected is epoxidized soybean oil-modified polyether polyol with a molecular weight of 6000 and a functionality of 3; and the isocyanate content of the polymerized MDI is 28%.

[0076] The inorganic filler comprises the following raw materials in parts by weight: 20 parts of calcium carbonate, 10 parts of aluminum nitride, and 5 parts of silicon carbide. The particle size distribution of the aluminum nitride filler is 120-150 nm, and the particle size distribution of the silicon carbide filler is 450-500 nm.

[0077] The preparation method of the above-mentioned polyurethane potting adhesive with high thermal conductivity and low expansion coefficient comprises the following steps:

[0078] (1) Preparation of component A:

[0079] According to the formula, the modified castor oil, the polyether polyol modified by epoxy soybean oil, the inorganic filler and the pigment in component A are weighed respectively; the weighed components are put into a disperser, the temperature is raised to 80° C., and the disperser is stirred for 1 hour. Then, the disperser is evacuated and stirred to remove water for 1 hour to obtain component A.

[0080] According to the mass ratio of component A to component B of 8:1, weigh component B.

[0081] (2) Preparation of polyurethane potting compound with high thermal conductivity and low expansion coefficient

[0082] After mixing and stirring component A and component B, put them into a vacuum degassing machine, evacuate to -0.1Mpa, and perform vacuum mixing and stirring degassing. After the vacuum stirring and degassing process is repeated 3 times, pour them into a mold and cure them at 70°C for 4 hours to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0083] Example 4

[0084] A polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising component A and component B;

[0085] Component A comprises the following raw materials in parts by weight: 10 parts of epoxidized castor oil, 15 parts of hydrogenated castor oil, 10 parts of succinic acid-modified castor oil, 80 parts of epoxidized soybean oil-modified polyether polyol, 40 parts of inorganic filler, 1 part of iron blue, 1 part of iron yellow, and 1 part of iron red.

[0086] Component B comprises the following preparation raw materials in parts by weight: polymeric MDI.

[0087] The mass ratio of component A to component B is 8:1.

[0088] The castor oil used is epoxidized castor oil with a molecular weight of 1000 and a hydroxyl value of 192 mgKOH / g; hydrogenated castor oil with a molecular weight of 1500 and a hydroxyl value of 200 mgKOH / g and succinic acid-modified castor oil with a molecular weight of 1800 and a hydroxyl value of 160 mgKOH / g; the epoxidized soybean oil-modified polyether polyol uses an epoxidized soybean oil-modified polyether polyol with a molecular weight of 4000 and a functionality of 3, and the isocyanate content of the polymerized MDI is 25%.

[0089] The inorganic filler comprises the following raw materials in parts by weight: 25 parts of calcium carbonate, 5 parts of aluminum nitride, 5 parts of silicon carbide, and 5 parts of aluminum oxide. The particle size distribution of the aluminum nitride filler is 120-150 nm, the particle size distribution of the silicon carbide filler is 450-500 nm, and the particle size distribution of the aluminum oxide filler is 200-300 nm.

[0090] The preparation method of the above-mentioned polyurethane potting adhesive with high thermal conductivity and low expansion coefficient comprises the following steps:

[0091] (1) Preparation of component A:

[0092] According to the formula, the modified castor oil, the polyether polyol modified by epoxy soybean oil, the inorganic filler and the pigment in component A are weighed respectively; the weighed components are put into a disperser, the temperature is raised to 80° C., and the disperser is stirred for 1 hour. Then, the disperser is evacuated and stirred to remove water for 1 hour to obtain component A.

[0093] According to the mass ratio of component A to component B of 8:1, weigh component B.

[0094] (2) Preparation of polyurethane potting compound with high thermal conductivity and low expansion coefficient

[0095] After mixing and stirring component A and component B, put them into a vacuum degassing machine, evacuate to -0.1Mpa, perform vacuum mixing and stirring degassing, stir evenly at a speed of 800-1000 rpm, repeat the vacuum stirring and degassing process 3 times, pour them into a mold, and cure them at 70°C for 3 hours to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0096] Comparative Example 1

[0097] A polyurethane potting adhesive comprises a component A and a component B;

[0098] Component A comprises the following raw materials in parts by weight: 10 parts of common castor oil, 100 parts of polyether polyol, 10 parts of inorganic filler, and 5 parts of iron red.

[0099] Component B comprises the following preparation raw materials in parts by weight: polymeric MDI.

[0100] The mass ratio of component A to component B is 8:1;

[0101] The castor oil used is ordinary castor oil with a molecular weight of 900 and a hydroxyl value of 210 mgKOH / g; the polyether polyol used is a polyether polyol with a molecular weight of 8000 and a functionality of 5; and the isocyanate content of the polymerized MDI is 19%.

[0102] The inorganic filler comprises the following raw materials in parts by weight: 5 parts of calcium carbonate, 1 part of aluminum nitride, 1 part of silicon carbide, and 2 parts of aluminum oxide. The particle size distribution of the aluminum nitride filler is 15 μm, the particle size distribution of the silicon carbide filler is 20 μm, and the particle size distribution of the aluminum oxide filler is 50 μm.

[0103] The preparation method of the above-mentioned polyurethane potting adhesive with high thermal conductivity and low expansion coefficient comprises the following steps:

[0104] (1) Preparation of component A:

[0105] According to the formula, castor oil, polyether polyol, inorganic filler and pigment in component A are weighed respectively; the weighed components are put into a disperser, heated to 80° C., dispersed and stirred for 1 hour, and then the disperser is evacuated and stirred to remove water for 1 hour to obtain component A.

[0106] According to the mass ratio of component A to component B of 8:1, weigh component B.

[0107] (2) Preparation of polyurethane potting compound with high thermal conductivity and low expansion coefficient

[0108] After mixing and stirring component A and component B, put them into a vacuum degassing machine, evacuate to -0.1MPa, perform vacuum mixing and stirring degassing, and stir evenly at a speed of 800-1000 rpm. After the vacuum stirring and degassing process is repeated 3 times, pour them into a mold and cure them at 70°C for 3h to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0109] Comparative Example 2

[0110] A polyurethane potting adhesive comprises a component A and a component B;

[0111] Component A comprises the following raw materials in parts by weight: 60 parts of modified castor oil, 50 parts of polyether polyol, 55 parts of inorganic filler, 2 parts of iron blue, 1 part of iron yellow, and 2 parts of iron red.

[0112] Component B comprises the following preparation raw materials in parts by weight: polymeric MDI.

[0113] The mass ratio of component A to component B is 8:1;

[0114] The castor oil used is oleic acid-modified castor oil with a molecular weight of 2000 and a hydroxyl value of 152 mgKOH / g; the polyether polyol used is peanut oil-modified polyether polyol with a molecular weight of 8000 and a functionality of 5; and the isocyanate content of the polymerized MDI is 19%.

[0115] The inorganic filler comprises the following raw materials in parts by weight: 5 parts of calcium carbonate, 20 parts of aluminum nitride, 20 parts of silicon carbide, and 10 parts of aluminum oxide. The particle size distribution of the aluminum nitride filler is 30 μm, the particle size distribution of the silicon carbide filler is 15 μm, and the particle size distribution of the aluminum oxide filler is 50 μm.

[0116] The preparation method of the above-mentioned polyurethane potting adhesive with high thermal conductivity and low expansion coefficient comprises the following steps:

[0117] (1) Preparation of component A:

[0118] According to the formula, castor oil, polyether polyol, inorganic filler and pigment in component A are weighed respectively; the weighed components are put into a disperser, heated to 80° C., dispersed and stirred for 1 hour, and then the disperser is evacuated and stirred to remove water for 1 hour to obtain component A.

[0119] According to the mass ratio of component A to component B of 8:1, weigh component B.

[0120] (2) Preparation of polyurethane potting compound with high thermal conductivity and low expansion coefficient

[0121] After mixing and stirring component A and component B, put them into a vacuum degassing machine, evacuate to -0.1MPa, perform vacuum mixing and stirring degassing, and stir evenly at a speed of 800-1000 rpm. After the vacuum stirring and degassing process is repeated 3 times, pour them into a mold and cure them at 70°C for 3h to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0122] Comparative Example 3

[0123] A polyurethane potting adhesive comprises a component A and a component B;

[0124] Component A comprises the following raw materials in parts by weight: 30 parts of modified castor oil, 70 parts of polyether polyol, 15 parts of inorganic filler, and 0.5 parts of iron red.

[0125] Component B comprises the following preparation raw materials in parts by weight: polymeric MDI.

[0126] The mass ratio of component A to component B is 8:1;

[0127] The castor oil used is stearic acid-modified castor oil with a molecular weight of 3000 and a hydroxyl value of 133 mgKOH / g; the polyether polyol used is olive oil-modified polyether polyol with a molecular weight of 3000 and a functionality of 2; and the mass content of isocyanate in the polymerized MDI is 37%.

[0128] The inorganic filler comprises the following raw materials in parts by weight: 5 parts of aluminum nitride, 5 parts of silicon carbide, and 5 parts of aluminum oxide. The particle size distribution of the aluminum nitride filler is 20 μm, the particle size distribution of the silicon carbide filler is 20 μm, and the particle size distribution of the aluminum oxide filler is 50 μm.

[0129] The preparation method of the above-mentioned polyurethane potting adhesive with high thermal conductivity and low expansion coefficient comprises the following steps:

[0130] (1) Preparation of component A:

[0131] According to the formula, the modified castor oil, polyether polyol, inorganic filler and pigment in component A are weighed respectively; the weighed components are put into a disperser, heated to 80° C., dispersed and stirred for 1 hour, and then the disperser is evacuated and stirred to remove water for 1 hour to obtain component A.

[0132] According to the mass ratio of component A to component B of 8:1, weigh component B.

[0133] (2) Preparation of polyurethane potting compound with high thermal conductivity and low expansion coefficient

[0134] After mixing and stirring component A and component B, put them into a vacuum degassing machine, evacuate to -0.1Mpa, perform vacuum mixing and stirring degassing, stir evenly at a speed of 800-1000 rpm, repeat the vacuum stirring and degassing process 3 times, pour them into a mold, and cure them at 70°C for 3 hours to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

[0135] Table 1 Performance test results of polyurethane potting glue of examples and comparative examples

[0136]

[0137] It can be seen from the above examples that Examples 1 to 4 of the present invention all have lower hardness, indicating that their damping effect is better, and the thermal conductivity is higher than that of the comparative example, indicating that the potting glue prepared by the example has a better thermal conductivity. Examples 1 to 4 all have lower expansion coefficients and higher tensile strengths, indicating that the potting glue prepared by the example has a small volume change with temperature after potting, and can withstand higher internal stress. Examples 1 to 4 all have lower viscosity, indicating that the potting glue prepared by the example has better construction performance. Comparative Examples 1 to 3 have a larger expansion coefficient relative to the examples, but a lower tensile strength and a higher viscosity, indicating that their processing performance and use performance are relatively poor.

[0138] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polyurethane potting adhesive with high thermal conductivity and low expansion coefficient, comprising component A and component B; the mass ratio of component A to component B is 7.8-8.2:1; In parts by weight, the component A comprises 60-90 parts of epoxy soybean oil-modified polyether polyol, 20-50 parts of modified castor oil, 20-50 parts of inorganic filler and 1-3 parts of pigment; The molecular weight of the epoxy soybean oil-modified polyether polyol is 4000-6000, and the functionality is 2.5-4.5; The modified castor oil is one or more of succinic acid-modified castor oil, hydrogenated castor oil and epoxidized castor oil; the molecular weight of the modified castor oil is 900-1800, and the hydroxyl value is 160-200 mgKOH / g; The inorganic filler comprises calcium carbonate and nano-inorganic matter; the nano-inorganic matter is selected from one or more of nano-aluminum oxide, nano-silicon carbide and nano-aluminum nitride; the particle size of the nano-inorganic matter is 100-500nm; the mass ratio of the calcium carbonate to the nano-inorganic matter is 1-3:1; The B component is polymeric MDI.

2. The polyurethane potting adhesive according to claim 1, characterized in that: The mass content of isocyanate in polymeric MDI is 20~35%.

3. A method for preparing the polyurethane potting adhesive with high thermal conductivity and low expansion coefficient according to any one of claims 1 to 2, comprising the following steps: The epoxy soybean oil-modified polyether polyol, modified castor oil, inorganic filler and pigment are mixed, heated to 80-120° C., stirred for 0.5-1.5 h, and then water is removed to obtain component A; After the A component and the B component are mixed, the mixture is evacuated to -0.095-0.1 MPa, stirred evenly at 600-1200 rpm, degassed, and cured to obtain a polyurethane potting adhesive with high thermal conductivity and low expansion coefficient.

Citation Information

Patent Citations

  • Solvent-free double-constituent polyurethane compound adhesive and preparation method for same

    CN103013417A

  • Double-component solvent-free polyurethane structural adhesive coated at normal temperature, as well as preparation method and application method thereof

    CN104449538A